Cyber dating abuse and ghosting behaviours: personality and gender roles in romantic relationships - Roberta Biolcati; Virginia Pupi; Giacomo Mancini (Current Issues in Personality Psychology, 2021)
Background Cyber dating abuse (CDA) refers to physical, verbal, and psychological violence perpetrated towards a romantic part-ner via technology and social media. Another emerging form of online abuse is ghosting, a silent strategy to dissolve undesired relationships without openly having to break them up. The aims of the current study were (i) to explore the relationship between CDA and ghosting behaviours in romantic relationships and (ii) to investigate the roles of gender and personality traits (conscientiousness, agreeableness, extraversion, emotional stability, openness) in pre-diction of CDA (perpetration and victimization)